Expression Of Recombinant Denv Ns2b/Ns3 Protease: In Silico Screening And In Vitro Validation Of Novel Antiviral Compounds For Dengue Virus Inhibition - Harun, Norshidah (2024)
Globally, the relentless rise in dengue cases worldwide has been further intensified and inadvertently neglected in the backdrop of the persistent covid-19 pandemic. Despite the escalating global impact of dengue virus (denv) infection, there remains a conspicuous absence of its effective treatment. Hence, the exploration and advancement of dengue antiviral treatments remain a primary focus of research. An appealing target for the anti-denv drugs is the virally encoded trypsin-like serine protease (ns3pro) and its related cofactor (ns2b). The denv ns2b/ns3 protease complex is responsible for cleaving the viral polyprotein into distinct functional viral proteins, making it crucial for virus replication. In the past 15 years, the production of an active denv ns2b/ns3 pro has mostly relied on constructs that link the cterminus of the hydrophilic cofactor domain of ns2b to the n-terminus of ns3 pro using a flexible glycine linker. Despite thorough analysis, no potential inhibitory drugs have been discovered thus far. Furthermore, the impact of the synthetic linker introduced between the protease and its cofactor remains uncertain. Recently, an alternative strategy for producing a catalytically active denv ns2b/ns3 pro complex that is not covalently connected has been reported by professor paul young from the university of queensland, australia, and his team. By employing the non-covalent plasmid construct, this study successfully expressed and purified a high-solubility protein of recombinant denv ns2b/ns3 pro under optimal conditions, with betaine supplementation.